2006
DOI: 10.2307/4134535
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Phylogenetic Analyses of Phenoloxidases from Brachyuran (Cancer magister) and Branchiopod (Artemia franciscana, Triops longicaudatus) Crustaceans

Abstract: Arthropod phenoloxidases catalyze the melanization and sclerotization of the new postmolt exoskeleton, and they function in the immune response. Hemocyanin, phylogenetically related to phenoloxidase, can function as a phenoloxidase under certain conditions. We investigated the relative contributions of hemocyte phenoloxidase and hemocyanin in the brachyuran crab Cancer magister, using the physiological ratio at which they occur in the hemolymph, and found that hemocyte phenoloxidase has higher activity. They b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 62 publications
3
50
2
Order By: Relevance
“…However, this would suggest that there had to have been little to no PPO in the HLS to propagate such a reaction. This would be contrary to the findings of Terwilliger and Ryan (2006) who noted that in assessments of PO and hemocyanin (a PPO phylogenetically related to PO) isolated from hemolymph of the brachyuran crab Cancer magister (Terwillinger et al, 2006), both the PO and hemocyanin found in hemocytes could convert diphenols to O-quinones and that the hemocyanin appeared to be present 'in [a] much higher concentration' . Similarly, PO activity in spiny lobster (Panulirus argus) hemolymph was due to a presence of PPO in hemocytes and hemocyanin in the plasma (Perdomo-Morales et al, 2007).…”
Section: Discussioncontrasting
confidence: 54%
“…However, this would suggest that there had to have been little to no PPO in the HLS to propagate such a reaction. This would be contrary to the findings of Terwilliger and Ryan (2006) who noted that in assessments of PO and hemocyanin (a PPO phylogenetically related to PO) isolated from hemolymph of the brachyuran crab Cancer magister (Terwillinger et al, 2006), both the PO and hemocyanin found in hemocytes could convert diphenols to O-quinones and that the hemocyanin appeared to be present 'in [a] much higher concentration' . Similarly, PO activity in spiny lobster (Panulirus argus) hemolymph was due to a presence of PPO in hemocytes and hemocyanin in the plasma (Perdomo-Morales et al, 2007).…”
Section: Discussioncontrasting
confidence: 54%
“…There is mounting evidence to suggest the amphipods and isopods (peracarids) lack a sensu strictu prophenoloxidase, and instead it has been suggested that hemocyanins of these organisms, which diverged from other crustacean hemocyanins ca. 285 Mya (48) act as both oxygen carriers and phenoloxidases (44,49,50). We were not able to find ESTs for prophenoloxidases in the hepatopancreas transcriptome, nor for any other oxidases such as peroxidases or laccases that might be expected to fulfill a role in lignin degradation, but note that the hemocyanins ESTs are particularly abundant.…”
Section: And Coptotermes Formosanus (Bab40696) Gastropod Sequences Imentioning
confidence: 79%
“…Phenoloxidases are required for a range of functions in crustaceans, including immune responses, and sclerotization and melanization of the exoskeleton (44), and in most cases, a prophenoloxidase located in the hemocytes is responsible for these activities. These prophenoloxidases are copper-containing enzymes that are closely related to the oxygen transporter hemocyanin.…”
Section: And Coptotermes Formosanus (Bab40696) Gastropod Sequences Imentioning
confidence: 99%
“…Nevertheless, the presence of hemocyanin provides convincing evidence that the Planorbidae did descend from blue-blooded ancestors. A co-occurrence of hemoglobin and hemocyanin is highly unusual and has been reported only in the amphipod Cyamus scammoni, in the phylum Arthropoda (15). By a combination of EST data and RT-PCR with primers based on the known sequence of B. glabrata myoglobin (16), we generated and sequenced cDNAs encoding two complete hemoglobin polypeptides, termed BgHb1 and BgHb2.…”
Section: Resultsmentioning
confidence: 99%